COORDENAÇÃO MODULAR EM ALVENARIA ESTRUTURAL: NECESSIDADES E PARTICULARIDADES DA CADEIA PRODUTIVA DE BLOCOS CERÂMICOS ESTRUTURAIS EM MINAS GERAIS - Cesar, Cristina Guimarães; Noronha, Marcela Michelini (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This study has the objective to evaluate if the ceramic structural blocks manufactured in Minas Gerais comply with the NBR 15873:2010 related to the modular coordination for building construction , and also identifying the perception of the manufacturers about this norm. For that, it was made a research about the ceramic structural blocks dimensions manufactured by five companies of the state and representatives of these companies were interviewed in order to understand their opinion about the modular coordination norm, the concepts related to it and the challenges to its application. It was verified that only two of the companies offer blocks modularly coordinated and among all the dimensions manufactured by these five companies only 19,1% are based on the norm. During the interviews, it was verified that none of the representatives was fully aware about the concepts of NBR 15873:2010. Three of them reported that never heard about this norm. The results obtained indicate that to define an efficient strategy to implement the modular coordination norm, it is necessary a greater spread of information to the manufacturers, and also to identify and mitigate the obstacles to adhere to the standard.